Sex-specific nitrogen allocation tradeoffs in the leaves of Populus cathayana cuttings under salt and drought stress - Liu, Miao (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2022 Elsevier Masson SAS. All rights reserved.